Proposed collection development policy statement for Claret School of Quezon City High School Library - Pujol, Yulysses V. (2004)
The Claret School of Quezon city High School Library is an independent and non-profit institution modeled to support the information needs of the students, faculty members and personnel of the Claret School of Quezon City High School. It is therefore understood that the main responsibility of the head librarian is to provide information that will support the curriculum and as well as personal needs. But before the librarian do all these tasks, it is necessary for him/her to be guided by some policies to ensure that he/she is getting the right materials. In order to identify what kind of materials should be included in the collection a set of rules or guidelines for the development of the library's resources must be created.